Chronic bronchitis--measurements and observations over 10 years. Issue 1 (February 1976) - Johnston, R N; McNeill, R S; Smith, D H; Legge, J S; Fletcher, F
Abstract : A total of 111 patients with chronic bronchitis were selected for study in 1963. By 1974 only 54 patients were available for clinical examination, chest radiography, and pulmonary function measurements. There was a significantly higher mortality compared with men of the same age and in the same locality, and this was due to cardiorespiratory failure and bronchial carcinoma. Reduction of cigarette smoking, declining atmospheric pollution, and antibiotic treatment have reduced the 24-hour sputum volume of these patients. The initial one-second forced expiratory volume (FEV1) and vital capacity were significantly lower in those patients who later died from cardio-respiratory failure. The duration of antibiotic treatment and the smoking record have not significantly affected the decline of the FEV1 with advancing age. The transfer factor (diffusing capacity) for carbon monoxide (TF) has declined more in those who continued to smoke. Of the 54 patients 14 had radiological evidence of emphysema initially. This has shown little change over 10 years.